The Class of Pregnant Women Influences the Knowledge and Attitudes of Pregnant Women Toward PITC HIV/AIDS - Siswarini, Lusi Sulfiana; Kholisotin, Kholisotin; Agustin, Yuana Dwi (Poltekkes Kemenkes Kupang, 2019)
Background: HIV is currently one of the threats of the virus in pregnant women. Mothers can transmit the virus to their children during pregnancy, childbirth or while breastfeeding. Prevention can be done by requiring pregnant women to take an HIV test during pregnancy. This activity is very important in an effort to increase public awareness about HIV and AIDS in order to prevent the spread of HIV infection. The purpose of this study was to determine the effect of the implementation of the class of pregnant women on the knowledge and attitudes of pregnant women in the PITC HIV / AIDS examination at Tenggarang Health Center, Bondowoso Regency. Method: This study uses a pre-experimental design, and data analysis uses the Wilcoxon test. The respondents of this study consisted of 86 pregnant women who were collected by total sampling technique. Result: The results showed that before and after the classes of pregnant women there was an increase in knowledge of the good categories by 24 respondents (27.9%) to 63 respondents (73.3%). The attitude with a positive category was 37 respondents (43.0%) to 71 respondents (82.6%). Conclusion: So it can be concluded that there is a significant influence before and after the implementation of the class of pregnant women on the knowledge and attitudes of pregnant women in the PITC HIV / AIDS examination.